The turnaround of Swedish industry: Reforms, firm diversity and job and productivity dynamics - Fredrik Heyman; Pehr-Johan Norbäck; Lars Persson (Research Institute of Industrial Economics (IFN), 2015)
In this paper, we argue that fundamental reforms of the Swedish business sector can explain the remarkable productivity and employment growth that followed the deep economic crisis in Sweden in the early 1990s. In the 1970s and 1980s, Sweden had one of the most regulated business sectors in the developed world. In the 1990s, however, Sweden reformed its labour market, product market, and corporate tax system as well as removed barriers to foreign direct investment (FDI). Our main finding from our institutional and theoretical examination is that the removal of barriers to entry and growth for new and productive firms and the increased rewards for investments in human capital and effort in workplaces were crucial to the success of these reforms. We find support for our thesis using detailed matched plant-firm-worker data. In particular, we observe increased allocative efficiency, measured as increased market share for more productive firms. Moreover, we show that foreign firms substantially contributed to productivity and employment growth during this period, which suggests that the liberalization of FDI was an important factor in the success of the reforms. Finally, we discuss how other countries can benefit from the Swedish experience by examining factors that appear to be specific to Sweden and others that can be generalized to other countries.
Keywords: D22; E23; J21; J23; K23; L11; L16; L51; 330; regulations; allocative efficiency; productivity; job dynamics; matched employer-employee data; industrial structure and structural change